Sustainable Development Goals and Islamic Finance: An Integrated Approach for Islamic Financial Institutions - Muhmad , Siti Nurain; Muhamad, Rusnah; Sulong, Farizah (Indonesian Journal of Sustainability Accounting and Management, 2021)
The challenges posed by environmental degradation and abandoning of social rights to secure business interests have highlighted the importance of focusing on sustainable development within the global financial system, especially among citizens and policymakers. The timely declaration of the Sustainable Development Goals (SDGs) by the United Nations is appropriate in addressing environmental degradation. In fact, the SDGs have become part of the fundamental agenda and essential requirements of every business, including Islamic financial institutions. In particular, the concept of sustainable development is parallel with Islamic teachings, which promote welfare, security, and rights for the sake of the current and future generations. Furthermore, Islamic finance and the SDGs are closely associated, as the former is capable of serving a meaningful function in sustainable development to achieve the goals of implementing fair and equitable tools, promoting resource mobilization, and enabling social benefit tools. Therefore, this study highlights an important case for Islamic financial institutions by expounding on the best indicators for sustainable Islamic finance.